Enhanced thermal conductivity for polybenzoxazine matrix composites by constructing a hybrid conductive network and modification of fillers. Issue 7 (8th February 2021) - Pei, Yaran; Lin, Xiao; Gong, Hongyu; Zhang, Yujun; Chen, Guowen; Feng, Yurun; Saleem, Adil; Jing, Jie; Yang, Rongkun; Wang, Shan; Sheng, Mingming; Zhang, Xinfeng; et al.
Abstract: Polyhedral oligomeric silsesquioxanes (POSS) and γ-glycidoxy propyl trimethoxy silane (KH560) were applied to modify boron nitride (BN) and boron nitride whisker (BNw ), and modified BN (m-BN) and modified BNw (m-BNw ) were added as thermally conductive fillers to polybenzoxazine (PBz) matrix to synthesize m-BN/m-BNw /PBz composite by hot press. The research results indicate that the modification of BN and BNw and the synergistic effect between m-BN and m-BNw can significantly improve the thermal conductivity of PBz composite. The thermal conductivity of PBz composite with 25 wt % m-BN and 25 wt % m-BNw reached to 1.27 W/mK, which is 35% higher than PBz composite with 50 wt % m-BN (0.94 W/mK), 76% higher than PBz composite with 50 wt % BN (0.72 W/mK), and also display excellent electrical insulation performance. The corresponding dielectric constant (ε) and dielectric loss (tan δ) were 3.83 and 0.0078, respectively. Besides, the Theat-resistance index (THRI ) of PBz composite with 25 wt % m-BN and 25 wt % m-BNw is 242.26 °C, and the thermal degradation temperature at 30% weight loss (T30 ) is 557.72 °C, are higher than PBz matrix (224.46 and 498.88 °C). And the tensile strength of PBz composites with 25 wt % m-BN and 25 wt % m-BNw is 47.71 MPa. Graphical Abstract: UF0001